Perception and Practices of Nurses about Diabetic Foot Care - Das, Jharna Rani (Ibrahim Cardiac Medical Journal, 2021)
Background & objective: Diabetic-foot care or diabetic foot ulcer (DFU) care is a vital aspect of care for diabetic patients. It is conceived that nurses placed in a diabetic hospital are knowledgeable and efficient in the management of diabetic ulcer care. But how efficiently they are providing this service has not yet been formally evaluated. The present study was undertaken to evaluate the nurses’ “diabetic foot care behavior” at the BIRDEM (Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders), Dhaka. Methods: This study was carried out on nurses having at least one year of experience in “diabetic foot” care (preventive, curative and rehabilitative services) in BIRDEM General Hospital (the largest Diabetic Footcare Hospital in Bangladesh) between July 2019 to December 2019. A total of 207 Senior Staff nurses or nurses working in the surgical wards or in the outpatient departments (OPDs) were consecutively included in the study. A pre-structured questionnaire was used to assess the knowledge, attitude, and practices of nurses pertaining to diabetic foot care. The questionnaire, among others, included variables like age, gender, professional experience, and qualifications. The knowledge section comprised 15 items focusing on risk factors, descriptions, and the management of diabetic ulcers. The options provided for each question were “True,” or “False,”. A score of ‘1’ was given for each correct answer and ‘0’ for each wrong answers. All the 15 responses were then summed up to find the integrated score obtained by the respondents. The summed-up score was then converted into percentage of score obtained. The knowledge level of the respondents was evaluated in terms of Likert scale 0-4, where ‘0’ means poor knowledge (knowledge score ≤ 60%) and ‘4’ means highly satisfactory level of knowledge (knowledge score 91-100%) and ‘1’, ‘2’ and ‘3’ means fair (knowledge score 61-70%), average (knowledge score 71-80%) and satisfactory knowledge (knowledge score 81-90%) respectively. Results: About 50% of the respondents were 40 or > 40 years old with mean age of the respondents being 37.4±10.4 years. The respondents were predominantly female (80%) married (75.4%). Approximately 80% of the respondents had diploma (basic nursing degree) degree alone, 14.5% obtained graduate (BSc Nursing) degree as well. Over half (51.1%) of the respondents had > 10 years of professional experience with average years of experience being 14.6 ± 0.7 years, but two-thirds (68.1%) had < 5 years and only 13% had > 10 years of wound-care experience. Nearly 40% had specific training on wound care. One-third (34.3%) of the nurses were placed in Internal Medicine Unit, 33.8% in Surgery Unit, 14.4% in Emergency Unit. Over two-thirds (68.6%) of the nurses were service nurses, 18.4% were supervisor, 3.9% were intensive care nurses and 8.2% were polyclinic nurses. The respondents’ level of knowledge was evaluated in terms Likert scale 0 – 4 (as described in the Methods section). Accordingly 30% of the respondents had poor, 8% fair, 47.1% average 2.9% satisfactory and 12% highly satisfactory level of knowledge. Conclusion: The study concluded that nurses generally possess an inadequate level of knowledge pertaining to DFUs, despite a positive attitude towards learning or acquiring knowledge about DFU and its care. A comprehensive educational program focusing on evidence-based practice is deemed necessary to ensure better clinical practices by the nurses. Ibrahim Card Med J 2020; 10 (1&2): 57-65